The Influence of Service Quality, Trust, and Company Image on Customer Loyalty at Bank Mandiri Tebet South Jakarta Branch - Ayumi Alica Putri; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze how much influence the quality of service, trust and company image on loyalty. This quantitative study used primary data obtained from the distribution of questionnaires to 100 respondents. Research methods with descriptive analysis and inferential analysis. Data analysis through several tests with instrument tests, multiple linear regression correlation analysis, model feasibility tests and hypothesis testing. The results of regression analysis in this study provide clues that a positive influence was found on purchasing decisions based on the results shown in the regression equation Y = 0.303 X1 + 0.253 X2 + 0.395 X3. In the results of the feasibility test of the model obtained, where the amount of significance value is 0.000 shown in the ANOVA table which means the model is feasible to be used in research based on the significance value obtained. The conclusion on the hypothesis is partially obtained the significance value on the service quality variable which is 0.000, while on the confidence variable where the magnitude is 0.004 and the significance result on the company's image variable which is 0.000. Therefore, it was partially concluded that the three independent variables in this study gained a positive and significant influence on customer loyalty at Bank Mandiri Tebet, South Jakarta. Management is advised to pay more attention to the company's image factor to focus more on improving reputation which in the end is expected to contribute more to increasing customer loyalty, because the company's image has the greatest contribution value in terms of influencing loyalty and in order to further improve the quality of its services must focus more on increasing the speed and responsiveness of employees so that the company's goals are The whole can be achieved.